Nucleoporin 85 interacts with influenza A virus PB1 and PB2 to promote its replication by facilitating nuclear import of ribonucleoprotein - Ling, Yue-Huan; Wang, Hao; Han, Mei-Qing; Wang, Di; Hu, Yi-Xiang; Zhou, Kun; Li, Yan (Frontiers in Microbiology, 2022)
Transcription and replication of the influenza A virus (IAV) genome take place in the nucleus of infected cells, which rely on host factors to aid viral ribonucleoprotein (vRNP) to cross the nuclear pore complex (NPC) and complete the bidirectional nucleocytoplasmic trafficking. Here, we showed that nucleoporin 85 (NUP85), a component of NPC, interacted with RNP subunits polymerase basic 1 (PB1) and polymerase basic 2 (PB2) in an RNA-dependent manner during IAV infection. Knockdown of NUP85 delayed the nuclear import of vRNP, PB1 and PB2, inhibiting polymerase activity and ultimately suppressing viral replication. Further analysis revealed that NUP85 assisted the binding of PB1 to nuclear transport factor Ran-binding protein 5 (RanBP5) and the binding of PB2 to nuclear transport factor importin α1 and importin α7. We also found that NUP85 expression was downregulated upon IAV infection. Together, our study demonstrated that NUP85 positively regulated IAV infection by interacting with viral PB1 and PB2, which may provide new insight into the process of vRNP nuclear import and a novel target for effective antivirals.